Perkawinan Beda Agama dalam Perspektif Teori Kepastian Hukum - Bishmo Tegar Woro Anjati Arya Wirarajasena (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
Marriage certainly has legal consequences, and if the religion is different, various problems will certainly arise. These problems affect the relationship between husband and wife and their children if they have children. In terms of juridical legal regulations regarding interfaith marriages, formally and legally, have not been clearly and firmly regulated in Law No. 1 of 1974 concerning Marriage, Article 2 paragraph 1 of the Marriage Law only states that the validity of a marriage must be carried out according to the laws of each religion and its beliefs. Legal certainty in regulating interfaith marriages in Indonesia still does not have normative legal certainty in legal texts related to marriage. This has clearly given rise to multiple interpretations of the law on interfaith marriages, whereas the unity of meaning in the legal text in a Law is absolute, there should be no double meaning in the legal text or Law, because legal certainty refers to the implementation of clear, permanent, consistent and consequential laws whose implementation cannot be influenced by subjective circumstances.